KEBIJAKAN FORMULASI DALAM MENANGGULANGI PELECEHAN SEKSUAL DI MEDIA SOSIAL DITINJAU DARI UNDANG-UNDANG NOMOR 12 TAHUN 2022 TENTANG TINDAK PIDANA KEKERASAN SEKSUAL - Gen Yaish Ibrahim; Ade Adhari (Fakultas Hukum Universitas Tarumanagara, 2022)
Along with the development of technology, crime has also evolved. Crime, which used to happen inconventional ways, is now expanding through cyberspace. Crime that happened in cyberspace alsoknown as cybercrime. Sexual harassment in social media or cyber harassment was a cybercrime thatwas often occured nowadays. In Indonesia, there are several applicable laws to countering the sexualharassment in social media, which are Indonesian Criminal Code (KUHP) and Law of ElectronicInformation and Transactions (UU ITE). Unfortunately, those applicable laws still have hugeweaknesses. Law of Sexual Violence Crimes (UU TPKS) comes as a specific law that against sexualviolence. Basically, Law of Sexual Violence Crimes (UU TPKS) can be used to deal sexual harrasmentin social media. But, this applicable law still has some weaknesses thus may obstructed thecountermeasures of sexual harassment in social media. The main issue of this paper is how policyformulation in tackling sexual harassment in social media viewed from Law Number 12 of 2022 aboutSexual Violence Crimes (UU TPKS)? The ef ort to counter sexual harassment in social media shouldbe formulated by observing the characteristic of those crime as a cybercrime. Sexual harassment insocial media should be formulated clearly, and the definition of sexual harassment in social media alsoought to be in the body of the Sexual Violence Crimes Law (UU TPKS). It aims to maximize thecountermeasures and prevention of sexual harassment in social media.